Safety and Efficacy of Granulocyte/Monocyte Apheresis in Steroid-Dependent Active Ulcerative Colitis with Insufficient Response or Intolerance to Immunosuppressants and/or Biologics [the ART Trial]: 12-week Interim Results. (27th January 2016) - Dignass, Axel; Akbar, Ayesha; Hart, Ailsa; Subramanian, Sreedhar; Bommelaer, Gilles; Baumgart, Daniel C.; Grimaud, Jean-Charles; Cadiot, Guillaume; Makins, Richard; Hoque, Syed; Bouguen, Guillaume; Bonaz, Bruno
Abstract: Background and Aims: Patients with active, steroid-dependent ulcerative colitis with insufficient response or intolerance to immunosuppressants and/or biologic therapies have limited treatment options. Adacolumn, a granulocyte/monocyte adsorptive apheresis device, has shown clinical benefit in these patients. This study aimed to provide additional clinical data regarding the safety and efficacy of Adacolumn in this patient subgroup. Methods: This single-arm, open-label, multicentre trial [ART] was conducted at 18 centres across the UK, France, and Germany. Eligible patients were 18–75 years old with moderate-to-severe, steroid-dependent active ulcerative colitis with insufficient response or intolerance to immunosuppressants and/or biologics. Patients received ≥ 5 weekly apheresis sessions with Adacolumn. The primary endpoint was clinical remission rate [clinical activity index ≤ 4] at Week 12. Results: In all, 86 patients were enrolled. At Week 12, 33/84 [39.3%] of patients in the intention-to-treat population achieved clinical remission, with 47/84 [56.0%] achieving a clinical response [clinical activity index reduction of ≥ 3]. Clinical remission was achieved in 30.0% of patients with previous immunosuppressant and biologic failure; steroid-free clinical remission and response were observed in 22.6% and 35.7% of these patients, respectively. Quality of life [Short Health Scale] significantly improved at Week 12 [ p < 0.0001]. The majority of adverse events were of mild/moderate intensity. Conclusions: At Week 12, Adacolumn provided significant clinical benefit in a large cohort of steroid-dependent ulcerative colitis patients with previous failure to immunosuppressant and/or biologic treatment, with a favourable safety profile. These results are consistent with previous studies and support Adacolumn use in this difficult-to-treat patient subgroup.